2017
DOI: 10.1108/ijebr-01-2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneursheep and context: when entrepreneurship is greater than entrepreneurs

Abstract: Purpose The purpose of this paper is to explain how context shapes what becomes entrepreneurial. Design/methodology/approach The paper is part of a longitudinal study over ten years, an ethnographic work including interviews, participating in meetings and shadowing. Texts and voices boiled down to transcripts and notes were sorted in NVivo. The empirical material was presented as a simple, short story, with the aim to question established assumptions and relations. The paper propose context as the unit for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 64 publications
6
91
0
8
Order By: Relevance
“…15 This study therefore describes a new concept, which can explain something hitherto overlooked. This study also fulfils an identified need to learn more about how entrepreneurship and context interact (Gaddefors and Anderson 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 This study therefore describes a new concept, which can explain something hitherto overlooked. This study also fulfils an identified need to learn more about how entrepreneurship and context interact (Gaddefors and Anderson 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Here the context is important because it shapes what becomes entrepreneurial; according to Gaddefors and Anderson (2017), context can determine what type of entrepreneurship emerges. However, it is not the context in general that is important, but what is specifically going on in that context, as entrepreneurship connects to and thus creates a raft of changes.…”
Section: Animatorship and Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…Were we to repeat this search and analysis today, I think we would find many more studies discussing entrepreneurship at local level, and with a few patterns evolving. For example, Steffen Korsgaard is developing an interesting research stream on resourcefulness and rural contexts (for example, Korsgaard, Ferguson and Gaddefors 2015;Korsgaard, Müller and Tanvig 2015;Müller and Korsgaard 2018); Johan Gaddefors studies the co-creation of contexts and entrepreneurship, offering ideas for future theorizing on spatial contextualization (for example, Gaddefors and Anderson 2017;Gaddefors and Cronsell 2009). The renewed consideration for local places may well result from the contextualizing turn in the field; it provides further input for the spatial context discussion.…”
Section: Places Places Places: Rethinking the Spatial Contextmentioning
confidence: 99%
“…To determine whether value accrues or decreases there is a need to understand who is involved, the type and organisation of the activity undertaken, the outcomes of the activity, and the where and when of its taking place. In short, one needs to understand the context of entrepreneurial activity (Welter, 2011;Gaddefors and Anderson, 2017).…”
Section: Prostitution and Escorting As Value-adding And Value-extractmentioning
confidence: 99%